Mahatma Gandhi’s Education: A Lesson on Philosophy and Cultural Barriers to Peace in Intercultural Societies-The Indian-Mauritian Case Study - GUNPUTH, Rajendra Parsad (Journal of Education and Vocational Research, 2014)
Cultural barriers2 in terms of castes, religions and politics have been a major obstacle to most Hindus especially in inter-multicultural countries like India or Mauritius with serious impacts on peace. And any international organisation, especially the UNESCO 3, would disprove it. However, are interculturality and peace4 related and if yes5 to what extent? In a contextual approach, this paper deals with cultural barriers to peace reflecting the revival of the doctrine of Indian avatars focusing on to what extent human rights may also include the doctrine of Mahatma Gandhi to achieve peace in a multicultural society 6? Cultural barriers to peace in a multicultural country like Mauritius had already been encountered in India by Mahatma Gandhi. Castes, religion, creed and colour and political appurtenance have undermined peace in India and we may be influenced of the work and philosophy of Mahatma Gandhi to inspire our political leaders, citizens and other religious groups to overcome the same barriers in the same way he did that is non-violence. However, Mahatma Gandhi has never been a political leader per se but a religious man instead. Through a contextual approach and without taboo, the co-authors try to reflect on the subject matter with particular reference to the Mauritian case study, to what extent Gandhi’s philosophy is useful and omnipresent today and to what extent it can shed light in our fragile inter-multicultural society to avoid tensions among the different and existing social, religious and political groups.